HUBUNGAN TERPAAN BERITA COVID-19 DI DKI JAKARTA DAN KOMPETENSI KOMUNIKASI ANIES BASWEDAN DENGAN TINGKAT KEPERCAYAAN MASYARAKAT DKI JAKARTA KEPADA ANIES BASWEDAN - Amanda Cinthya Lois; Sri Widowati Herieningsih (Interaksi Online, 2021)
DKI Jakarta is currently the province with the highest number of positive cases of Covid-19 in Indonesia. The target to make a positive curve sloping has not yet been achieved, because the positive curve in Jakarta has not shown a significant decline, and even tends to increase. This study aims to determine the relationship between Covid-19 news exposure in DKI Jakarta and Anies Baswedan's communication competence with the level of public trust in Anies Baswedan. The theory used is the Mass Communication Effect and Speech Act Theory. The sample data collection technique used nonprobability sampling with a sample size of 90 people. The test was carried out using Kendall's Tau B analysis. The results of the study showed that the significance value for the Covid-19 news exposure variable in DKI Jakarta was 0.210, which means that the two variables had no relationship. While the results of Anies Baswedan's communication competence variable showed a significance value of 0.000, which means that the two variables have a positive and close relationship. With these results, it was suggested to Anies Baswedan to improve his communication competence, especially on indicators that message can be easily understood by the public.